Pengaruh Literasi Digital dan Digital Payment Terhadap Pengembangan Usaha (Studi Kasus UMKM Di Pasar Tanah Abang) - Nirma Hellyatul Auwalia; Karuniana Dianta A.S; Agus Wibowo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to analyze "the influence of digital literacy and digital payments on business development (case study of MSMEs in the Tanah Abang market)". Problems that often occur in MSMEs are limited capital structure, weak use of access to technology that is not optimal, and lack of financial services. This research uses primary data using a questionnaire via Google Form. and analyzed using validity, reliability and path analysis tests using SPSS version 27. The study results confirm that digital literacy and digital payments have a positive and significant impact on business development. Thus, this study is consistent with the government's efforts to encourage the acceleration of the implementation of digital literacy and digital payments in developing the MSME digitalization program.